Combating a deadly menace : early experiences with a community-based arsenic mitigation project in Bangladesh - Chowdhury, A. M. Raza (Research monograph series ;, 2000)
Report of project "Action Research into Community-Based Arsenic Mitigation" implemented in Narayanganj and Jessore districts.